Teacher of Fergana state technical university (Journal of Pedagogical Inventions and Practices, 2025)
This article explores the effectiveness of debate-based instruction in developing metacognitive speaking strategies among non-philology students learning English. The study emphasizes the role of structured debates as an interactive pedagogical tool that promotes learners’ awareness of their own cognitive and communicative processes during oral speech production. Through debate activities, students are encouraged to plan, monitor, and evaluate their speaking performance, which contributes to the enhancement of fluency, coherence, argumentation skills, and critical thinking. The paper highlights how debate-based learning fosters learner autonomy, reflective thinking, and strategic competence, making it a valuable approach in English language teaching for non-philology students.